Urban river rehabilition - water quality and pollution loads of Sg. Tebrau, Johor - 342804 Maketab Mohamed; Zulkifli Yusop, 1961-; Zaini Ujang, Prof. Dato' Ir. Dr., 1965-; Water Environmental Planning Seminar (2002 : IIU, Kuala Lumpur ) (Skudai : Universiti Teknologi Malaysia, 2002)
07